Negative priming in word recognition: a context effect - Chawarski, M C; Sternberg, R J (Journal of experimental psychology. General, 1993)
In 5 experiments using a priming methodology, the role of contextual factors on Ss' performance in a word-recognition task was investigated. Ss read short stories, and then their recognition of words from the stories was tested. Effects of contextual factors on Ss' performance were examined by manipulating the context of the stories' presentation and by designing the experimental materials to weaken the effects of semantic relations between primes and targets, thereby enhancing Ss' opportunity to use contextual relations between the words. The overall results of all 5 experiments indicate that context influences the priming effect of close semantic relations. They can be interpreted as supporting cue-retrieval models of priming mechanisms.